Intravenous Versus Oral Dexamethasone Premedication in Preventing Paclitaxel Infusion Hypersensitivity Reactions in Gynecological Malignancies. Issue 7 (1st September 2013) - O'Cathail, Sean M.; Shaboodien, Roekshana; Mahmoud, Sarah; Carty, Karen; O'Sullivan, Patrick; Blagden, Sarah; Gabra, Hani; Whear, Sue; Kwon, Janice S.; Agarwal, Roshan
Abstract : Objective: Dexamethasone premedication is required with paclitaxel to prevent infusion-related hypersensitivity reactions (HSRs). Both oral dexamethasone (PO-D; 20 mg 12 and 6 hours before paclitaxel) and intravenous dexamethasone (IV-D; 20 mg 30 minutes before paclitaxel) regimens are used. The optimal premedication regimen and management of patients after HSR are unclear. Methods: Data on HSRs in women receiving paclitaxel, 175 mg/m 2, every 3 weeks at Imperial College Healthcare Trust from May 2011 to February 2012 were obtained from the pharmacy database. During this period, dexamethasone premedication for paclitaxel was administered orally (PO-D; 20 mg 12 and 6 hours before paclitaxel) from May to August 2011, then changed to intravenous dexamethasone (IV-D; 20 mg 30 minutes before paclitaxel) for 3 months, and then reverted to PO-D from November 2011. There were 93 and 55 patients who received PO-D and IV-D before paclitaxel, respectively. Hypersensitivity reaction rates were pooled with those from published studies for analysis. Gynecologic oncology centers in the UK and Canada were surveyed regarding premedication and post-HSR management. A Markov Monte-Carlo simulation model compared costs and benefits of different strategies. Results: Hypersensitivity reaction rates with PO-D and IV-D were 5.4% (5/93) versus 14.5% (8/55) ( P = 0.07) in Imperial College Healthcare Trust patients, and 6.8% (20/290) versus 14.1% (30/212) ( P = 0.009) on pooled analysis with data from 2 additional studies (502 patients), respectively. However, IV-D is the most common premedication regimen used in the UK and Canada (48.5% and 34.2% of centers). Post-HSR paclitaxel on a desensitization protocol is a cost-effective alternative to discontinuing paclitaxel altogether. Conclusion: Oral dexamethasone seems to be superior to IV-D in preventing HSRs. Post-HSR patients should be considered for desensitization.